The effects of the vibrational excitation on H plus ND(a1?, j0=2, v0=0,1,2) reaction - Hekim, Seda; Akpinar, Sinan; Simsek, Esra (Springer, 2019)
Reactions of vibrationally excited ND (a(1)Delta, j(0) = 2, v(0) = 0,1,2) molecule with H atom have been carried out on the modified NH2 potential energy surface (PES) for the (2)A ' excited state using Centrifugal Sudden approximation. The chemical reaction of ND (a(1)Delta) with H can proceed via the depletion ND + H -> N + HD and the exchange pathways ND + H -> NH + D. So, we present the time-dependent wave packet quantum scattering calculations of initial-state-resolved reaction probabilities, integral cross sections and initial state-selected reaction rate constants for exchange and depletion channels of the title reaction. For exchange reaction, it was found that vibrational excitation plays a very important role in the integral cross sections and rate constants.
Keywords: Molecular Physics and Chemical Physics